HCG stimulates angiogenic signals in lymphatic endothelial and circulating angiogenic cells. (August 2015) - Schanz, Andrea; Lukosz, Margarete; Hess, Alexandra P.; Baston-Büst, Dunja M.; Krüssel, Jan S.; Heiss, Christian
Highlights: Lymphatic endothelial and circulating angiogenic cells express the LH/hCG receptor. hCG induces lymphatic endothelial and circulating angiogenic cell migration. hCG stimulates HIF-1α and further angiogenic molecules in these cells. hCG could be involved in lymphangiogenesis. Circulating angiogenic cells may be recruited by hCG. Abstract: Human chorionic gonadotropin (hCG) has long been associated with the initiation and maintenance of pregnancy, where angiogenesis plays an important role. However, the function of hCG in angiogenesis and the recruitment of vascular active cells are not fully understood. In this study, the role of hCG and its receptor in circulating angiogenic and human endothelial cells, including lymphatic, uterine microvascular, and umbilical vein endothelial cells, was examined. Immunohistochemistry and immunoblot analysis were used to detect LH/hCG receptor expression and the expression of hCG-induced angiogenic molecules. HIF-1α was determined via ELISA and downstream molecules, such as CXCL12 and CXCR4, via real-time PCR. Chemotaxis was analyzed using Boyden chambers. Our results show that the LH/hCG receptor was present in all tested cells. Furthermore, hCG was able to stimulate LH/hCG-receptor-specific migration in a dose-dependent fashion and induce key angiogenic molecules, including HIF-1α, CXCL12, and CXCR4. In conclusion, our findings underscore the importance of hCG as one of the first angiogenic molecules produced by the conceptus. hCG itself alters endothelial motility, recruitment, and expression of pro-angiogenic molecules and may therefore play an important role in vascular adaption during implantation and early placental formation.